2019
DOI: 10.2147/ppa.s232935
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Negative Emotions Due to Chronic Illness Screening Test (NECIS): Construct Validity in Patients with Coronary Artery Disease in Mainland China</p>

Abstract: ObjectivePatients with coronary artery disease (CAD) are susceptible to the negative emotion and its adverse influence on the disease prognosis. It is of great necessity to have a simple measurement to timely assess negative emotions in patients with CAD. The Negative Emotions due to Chronic Illness Screening Test (NECIS) is a newly developed tool to measure negative emotions. However, the construct validity has not been established yet. Therefore, the purpose of this study was to test the construct validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Regarding the avoidance/denial subscale, before the educational intervention, it was found that participants at working age were more likely to be “unadjusted” in this subscale than retired users. In this regard Chen, Zhou, Liu, and Yu reported that feelings of denial are more frequent in people at working age, because chronic diseases can limit their performance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the avoidance/denial subscale, before the educational intervention, it was found that participants at working age were more likely to be “unadjusted” in this subscale than retired users. In this regard Chen, Zhou, Liu, and Yu reported that feelings of denial are more frequent in people at working age, because chronic diseases can limit their performance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%